Fetal Brain Magnetic Resonance Imaging Findings Predict Neurodevelopment in Children with Tuberous Sclerosis Complex - Hulshof, Hanna M; Slot, Emma M H; Lequin, Maarten; Breuillard, Delphine; Boddaert, Nathalie; Jozwiak, Sergiusz; Kotulska, Katarzyna; Riney, Kate; Feucht, Martha; Samueli, Sharon; Scholl, Theresa; Krsek, Pavel; et al. (The Journal of pediatrics, 2021)
OBJECTIVE: To correlate fetal brain magnetic resonance imaging (MRI) findings with epilepsy characteristics and neurodevelopment at 2 years of age in children with tuberous sclerosis complex (TSC) to improve prenatal counseling. STUDY DESIGN: This retrospective cohort study was performed in a collaboration between centers of the EPISTOP consortium. We included children with definite TSC, fetal MRIs, and available follow-up data at 2 years of age. A pediatric neuroradiologist masked to the patient's clinical characteristics evaluated all fetal MRIs. MRIs were categorized for each of the 10 brain lobes as score 0: no (sub)cortical lesions or doubt; score 1: a single small lesion; score 2: more than one small lesion or at least one large lesion (>5 mm). Neurologic manifestations were correlated to lesion sum scores. RESULTS: Forty-one children were included. Median gestational age at MRI was 33.3 weeks; (sub)cortical lesions were detected in 97.6%. Mean lesion sum score was 4.5. At 2 years, 58.5% of patients had epilepsy and 22% had drug-resistant epilepsy. Cognitive, language, and motor development were delayed in 38%, 81%, and 50% of patients, respectively. Autism spectrum disorder (ASD) was diagnosed in 20.5%. Fetal MRI lesion sum scores were significantly associated with cognitive and motor development, and with ASD diagnosis, but not with epilepsy characteristics. CONCLUSIONS: Fetal cerebral lesion scores correlate with neurodevelopment and ASD at 2 years in children with TSC.
Keywords: Magnetic Resonance Imaging; Epilepsy; Female; Infant; předškolní dítě; vývojové poruchy řeči; kognitivní poruchy; ženské pohlaví; lidé; magnetická rezonanční tomografie; těhotenství; následné studie; mozek; Cognition Disorders; neurovývojové poruchy; kohortové studie; Cohort Studies; retrospektivní studie; epilepsie; Tuberous Sclerosis; Follow-Up Studies; Language Development Disorders; kojenec; Brain; Child, Preschool; tuberózní skleróza; Neurodevelopmental Disorders; Pregnancy; Retrospective Studies; Humans